Pengaruh Kepemimpinan Kepala Sekolah dan Disiplin Kerja terhadap Kompetensi Profesional Guru - Haudi Haudi; Happy Fitria; Achmad Wahidy (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
The purpose of this study is to test the influence of principal's leadership and work discipline on the professional competence of teachers. This research is a quantitative. The paper used questionnaire and interview sheet as instrument. The result showed that principal's leadership and work discipline both partially and simultaneously influenced the professional competence of teachers. The paper recommends to more concern on principal's leadership and work discipline where the school would change professional competence of teachers.